2016
DOI: 10.1002/anie.201600480
|View full text |Cite
|
Sign up to set email alerts
|

Peptide [4]Catenane by Folding and Assembly

Abstract: A topologically complex peptide [4]catenane with the crossing number of 12 was synthesized by a folding and assembly strategy wherein the folding and metal-directed self-assembly of a short peptide fragment occur simultaneously. The latent Ω-looped conformation of the Pro-Gly-Pro sequence was found only when pyridines at the C- and N-termini coordinatively bind metal ions (Ag(I) or Au(I) ). Crystallographic studies revealed that the Ω-looped motifs formed four M3 L3 macrocycles that were intermolecularly entwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…[1,2] Inspired by the role of metals in the structure and functions of various types of proteins and peptides,extensive efforts have been made in the literature to design metal coordinated assemblies of proteins [3] and synthetic peptides. Nevertheless,F ujita and co-workers have demonstrated the metal driven stunning protein like channels, [6] bbarrels [7] as well as peptide catenanes [8] from short a-peptides. Nevertheless,F ujita and co-workers have demonstrated the metal driven stunning protein like channels, [6] bbarrels [7] as well as peptide catenanes [8] from short a-peptides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Inspired by the role of metals in the structure and functions of various types of proteins and peptides,extensive efforts have been made in the literature to design metal coordinated assemblies of proteins [3] and synthetic peptides. Nevertheless,F ujita and co-workers have demonstrated the metal driven stunning protein like channels, [6] bbarrels [7] as well as peptide catenanes [8] from short a-peptides. Nevertheless,F ujita and co-workers have demonstrated the metal driven stunning protein like channels, [6] bbarrels [7] as well as peptide catenanes [8] from short a-peptides.…”
mentioning
confidence: 99%
“…[4,5] Them etal triggered assembly of peptides [5d,e] and proteins [3e] offer ac ategorical approach to construct well defined nanostructures.H owever,u tilization of peptides to construct ordered metal-peptide-frameworks are scarcely examined. Nevertheless,F ujita and co-workers have demonstrated the metal driven stunning protein like channels, [6] bbarrels [7] as well as peptide catenanes [8] from short a-peptides. Thep rotein like quaternary structures have also been achieved from the metal coordinated assembly of synthetic coiled-coils [9] and collagen peptides.…”
mentioning
confidence: 99%
“…Recently, we reported that the short Pro-Gly-Pro (PGP) peptide sequence is folded into an "³"-shaped loop on concerted metal-coordination, and this gives rise to a highly entangled 12-crossing [4]catenane. 3 In this selfassembly, the latent ³-folding propensity of the PGP sequence is expressed by inter-strand interactions during the entanglement of the two loop motifs. To generalize this observation and demonstrate the potential of the folding-and-assembly strategy for creating highly complex discrete structures, we designed new ditopic heptapeptide ligand 1, in which PGP and GPP tripeptide sequences are linked through a rigid imino(1,3-phenylene)carbonyl spacer (Scheme 1).…”
mentioning
confidence: 99%
“…Some peptides exploit metal–ligand interactions to direct self‐assembly towards the formation of nanostructures with unique conformations and functionalities . Indeed, metal–ligand coordination is one of the most used interactions to drive the self‐assembly of small molecules as well as of synthetic peptides and proteins into various 2D and 3D supramolecular architectures—spanning from macrocycles and other geometrical shapes to cages and metal‐organic frameworks (MOFs), lattices, discs, spherical shells or fibrils, and additional quaternary structures ,. In recent years, a variety of oligomeric sequences akin to peptides, namely peptidomimetic foldamers, capable of binding metal ions have been developed, and some enabled biomimetic functions such as selective recognition, allosteric cooperativity, and catalysis .…”
Section: Methodsmentioning
confidence: 99%